Myofibrillogenesis Regulator-1 in Smooth Muscle Cells Modulates Inflammation Signaling Pathways via Regulating ROCK1 Ubiquitination and Degradation to Impact Aortic Dissection [Corrigendum] - Yin H; Li X; Lu D; Zhao X; Yang Z; Wang Z; Xu F; Chen Y; Li C (Journal of Inflammation Research)
Yin H, Li X, Lu D, et al. J Inflamm Res. 2025;18:1719–1738. The authors have advised there are clerical errors on pages 1720, 1721 and 1729 of the published paper. Specifically: Page 1720, line 4, the text “The intima, characterized” should read “The media, characterized”. Page 1721, Materials and Methods, Human Aortic Collection section, line 7, the text “confirmed by coronary CTA. Non-clamped aortic” should read “confirmed by aortic CTA. Non-AD aortic”. Page 1729, Figure 3 legend, line 5, the text “n=3” should read “NF-kappaB p65 phosphorylation activation was based on four independent experiments (n=4); all other data in this panel were based on n=3”. The authors have also advised the sentence “The duplication occurred in Figures 3A, 3C and 5C (β-actin) because the experimental conditions and sample sources for these groups were consistent” was missed from the legend of Figure 5 on page 1732. The correct legend and Figure 5 are as follows.